From Projects to Proficiency: How Project-Based Assignment Improve Student Understanding - Mahdiyah, Mahdiyah; Putri, Fildzah Rudyah; Dahlia, Mutiara (International Journal of Business, Law, and Education, 2022)
An assignment model in education refers to the framework or approach used to design, structure, and deliver tasks or assignments to students. This study explores the effectiveness of Project-Based Learning (PBL) in enhancing student understanding and proficiency. Over the course of a semester, 210 students in Universitas Negeri Jakarta from various disciplines were engaged in this research. Data were collected through assessment tests for two group of assignment model, namely PBL and Individual. The results showed that PBL significantly improves student understanding by promoting critical thinking, collaboration, and real-world application of knowledge. Students who participated in PBL showed greater retention of information and were more adept at applying concepts in practical scenarios compared to those who engaged in individual assignment models. These findings suggest that incorporating PBL into the curriculum can result in substantial improvements in student learning outcomes, making it a valuable pedagogical approach for educators